The big picture : medical biochemistry - Janson, Lee W., 1964- 4 0 16; Tischler, Marc.; 5 (New York : McGraw-Hill Medical, 2012)
A biochemistry review focusing on the concepts and techniques behind the diagnosis, prognosis and treatment of medical conditions, and includes progressive chapters, chapter overviews, tables and illustrations, and review questions.
Amino acids and proteins -- Carbohydrates -- Lipids -- Nucleosides, nucleotides, DNA, and RNA -- Functional biochemistry -- Enzymes and amino acid/protein metabolism -- Carbohydrate metabolism-- Lipid metabolism -- Membranes -- DNA/RNA function and protein synthesis -- Metabolism and vitamins/minerals -- The digestive system -- Muscles and motility -- Connective tissue and bone Blood -- The immune system -- The cardiovascular system -- The respiratory system -- The urinary system -- The nervous system -- The reproductive system.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Biochemistry.;Clinical biochemistry.;Biochemical Phenomena.;Biochemistry.;Clinical chemistry; 20; 2